(untitled) (American Journal of Medical Science and Innovation, 2024)
This study aimed to investigate the impact of excessive social media use on sleep and mental well-being among adults in Afghanistan. An online survey was conducted across 19 provinces in Afghanistan to assess social media usage and its effects on sleep. 407 Afghan adults Participated in the survey and were asked about their usage patterns, perceived addiction, and impact on their sleep quality and mental well-being. The survey revealed that many Afghan adults exhibited excessive social media usage and showed signs of addiction. ¾ participants reported a strong urge to use social media. Social media usage, particularly before bedtime, significantly affected sleep patterns and mental well-being. 68% of participants identified social media as a problem. A direct correlation was observed between the duration of social media usage and sleep disturbances, with increased usage leading to poor sleep quality and difficulty concentrating on daily activities. This study highlights the need for awareness and interventions to address the harmful effects of excessive social media use on sleep and mental well-being. Mental health professionals, policymakers, and health organizations are urged to collaborate and develop strategies to promote mental well-being and address the issue of excessive social media usage.